Deset starih mejnikov katastrskih občin vpisanih v Register kulturne dediščine - Triglav Čekada, Mihaela (Geodetski vestnik, 2024)
In the first months of 2024, on the initiative of the Geodetic Institute of Slovenia and the Surveying and Mapping Authority of the Republic of Slovenia, ten boundary marks of cadastral municipalities were registered in the national register of Cultural Heritage. They have in addition to their still valid geodetic role, also a cultural and historical significance. The inscribed landmarks are located in the vicinity of Sežana and Matarsko podolje. Matarsko Podolje.
Keywords: boundary mark of cadastral municipality; dediščina; heritage; mejnik katastrske občine; national register of cultural heritage; Register kulturne dediščine